Governance Challenges Constraining Business Process Management: The Case of a Large South African Financial Services Corporate - (:unkn) unknown (My University, 2020)
Obtaining and maintaining a competitive advantage is vital for profit-driven organizations. Business Process Management (BPM) and the governance thereof offer such organizations a framework of management practices within which to achieve this goal. The objectives of this study were to identify and describe the BPM governance challenges that constrain BPM in large South African corporates as BPM in South Africa had not previously received any comprehensive BPM governance focus. Additionally, the BPM and BPM governance bodies of knowledge lack literature on studies focused on BPM governance challenges. Qualitative research methods were utilized to collect useful and descriptive data through secondary document collection and interviews in a single case study. The study confirmed eight of the literature-identified governance challenge themes that constrain BPM and contributed eleven new BPM governance challenge themes to the BPM and BPM governance body of research.
Keywords: African Research